Cytogenetic and Cytotoxic Potentials of Borago officinalis on Albino Male Mice - Al-ezzy, Ruqaya Mohammed; alanee , Rafal Shakeeb; khalaf, Hadeel Mohamed (Iraqi Journal of Science, 2022)
The current study is an attempt to assess the cytogenotoxic potential of the ethanolic extract from the leaves of Borago officinalis on Swiss albino male mice. Young Swiss albino mice were orally administered with leaf ethanolic extract of Borago officinalis. Three mice groups were used using different doses of plant extract (T1: 100, T2: 200, and T3:400 mg) in addition to the control negative group (untreated mice) for 7 days to assess mitotic index or 28 days to assess meiotic index. The results revealed that the extract significantly induced the division of disruptive chromosomal changes in the bone marrow and the mean of abnormality was (3.5±0.47, 4.43±0.83, and 5.83±0.96%) for T1, T2, and T3 respectively, as well as in primary spermatocytes. It is planned that the extract might have interfered with the spindle protein or protein packing.